Temperance in Lincoln 1830 - 1870 - Paisana, Joanne (2005)
This chapter examines temperance/teetotal activity in the period 1830-70 in the relatively small English city of Lincoln. Placed in the rural county of Lincolnshire, where hops and barley were grown in profusion, its preponderance of brewers and drink sellers make it an interesting case study able to provide an alternative vision to the few tempertance studies made of large, industrial centres like Bradford and Manchester to date.